The Effect of Profitability, Earnings Per Share And Auditor's Reputation on Audit Delay With Company Size as Moderating Variables in Mining Companies Listed on The IDX Period 2015-2019 - Raymond Trilaksana, Ahmad; Fadjarenie, Agustin (Dinasti Publisher, 2021)
This study aims to analyze the effect of profitability, earnings per share and auditor reputation on audit delay by using firm size as a moderator. The study was conducted on 49 mining companies using certain criteria. Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA) were used for data analysis techniques. The results showed that the profitability and reputation of auditors had a significant effect on audit delay, while earnings per share did not. Firm size is also able to be a moderator for profitability and earnings per share on audit delay, while auditor reputation has no effect.